ENHANCING QESTIONS FORMATION SKILLS THROUGH DEFINITIONAL QUESTION ANSWERING (DQA) - Rifiyanti, Hafizah; Anggraeni, Noerlina; Dewi, Dyah Utami (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
Students often have difficulty in formulating questions that generate specific and definite answers. They lack proficiency in understanding and applying the grammatical structures and syntax required to form questions appropriately. This study aims to improve students' ability to formulate questions through the application of the Definitional Question Answering (DQA) learning method, where questions are designed to produce specific and definite answers. In this study, the experimental method was used to evaluate changes in students' abilities. The research sample consisted of 101 students majoring in management at the Faculty of Economics, Kosgoro Institute of Business and Informatics 1957 (IBIK 57). After intervention with the DQA program, a post-test was administered to assess the effectiveness of the program and students' progress. This study used an experimental design with a pre-test and post-test to evaluate the changes in students' abilities before and after the application of the DQA method. Before the application of the DQA method, all students took an initial test to measure their ability to formulate questions, comprehension of sentence elements, analytical ability, communication, and text comprehension. Thus, this study aims to contribute to improving students' skills in forming effective questions and deepening their understanding of the subject matter. The result is that the intervention or learning method that has been applied between the pre-test and post-test is effective in improving participants' performance